Durability behavior of steelmaking slag masonry mortars. (5th May 2016) - Santamaría-Vicario, I.; Rodríguez, A.; Junco, C.; Gutiérrez-González, S.; Calderón, V.
Abstract: A durability study is presented of masonry mortars prepared with varying quantities of electric-arc furnace slag (EAFS) and ladle furnace slag (LFS) in the same mixtures, in substitution of natural fine aggregate. The behavior of the mortars subjected to freeze-thaw cycles, wet-dry cycles, marine environments, salt crystallization tests, and industrial atmospheres (Kesternich test) is studied. Comparative results are reported for these different dosages of steel slag aggregates (between 25% and 100%), in substitution of natural fine aggregate in the mortars, which moreover employ commercial additives in their mixtures. Having finalized the accelerated aging tests, the specimens are tested under compression and flexion and their mechanical strengths after 90 days of curing compared with the mechanical strengths of the same materials without aging. The tests confirmed the long-term durability of the mortars that included large amounts of steel waste. These results can contribute to achieving the goals of maximum resource exploitation and progressive waste reduction towards which society is advancing. Graphical abstract: Highlights: Replacement of 100% of sand by steel slag allows achieving resistances over 15 MPa at 28 days. Compressive strength reaches more than 20 MPa at 90 days with increase in durability. Plasticiser reduces segregation while allowing the maintenance of the compressive strength to > 10 MPa. The use of water-retaining agent improves the workability with the absence of bleeding.